Relações dialógicas na constituição da escrita de artigos científicos - Silva, Fabrício José (2024)
Dialogical relationships are constitutive of language and, as such, can present themselves in different ways. Based on this assumption, in this work, we intend to show how these relationships can appear in academic writing production practices, especially in the writing of scientific articles. The texts examined to illustrate our debate come from a research corpus consisting of 18 (eighteen) scientific articles representing the three major areas of knowledge, namely: Biological, Exact and Human Sciences. These are scientific articles available in scientific journals representing these three major areas whose Qualis is positioned in stratum A1. In the investigation undertaken, we anchored ourselves in reflections from the Bakhtin Circle, especially expressed in the works Problems of Dostoevsky's Poetics (Bakhtin, 2018) and Marxism and Philosophy of Language (Volóchinov, 2021), from which we propose to analyze dialogical relationships having in view of the following aspects: (i) types of prose discourse (referent-oriented discourse, objectified discourse and double-voiced discourse); and (ii) the types and variants of discourse through which dialogical links are textualized. In assessing these aspects, we resorted to examples of modes of citation in the compositional construction of these articles, based, above all, on some Bakhtinian concepts methodologically used in the study of dialogical relationships, with a view to comparing the Circle's explanations with examples from scientific articles. Through this procedure, we note how dialogical relations can manifest themselves in the scientific article discourse genre, in order to also make it possible to see differences in the composition and scope of dialogical relations, by observing how different forms of citation in scientific articles can be explained in light of the notions of dialogical relationships and types and variants of discourse. Based on the analysis carried out, we also highlight the links and conflicts between one's own voice and the voice of others, between the voice that quotes and the one that is cited, thus configuring the role of dialogical relationships in the composition of the scientific article genre based on the different modes of citation found in these articles.